2018
DOI: 10.1007/s10695-018-0473-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to copper induces variable intensity of oxidative stress in goldfish tissues

Abstract: Copper is an essential element, but at high concentrations, it is toxic for living organisms. The present study investigated the responses of goldfish, Carassius auratus, to 96 h exposure to 30, 300, or 700 μg L of copper II chloride (Cu). The content of protein carbonyls was higher in kidney (by 158%) after exposure to 700 mg L copper, whereas in gills, liver, and brain, we observed lower content of protein carbonyls after exposure to copper compared with control values. Exposure to copper resulted in increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Our study further showed that the antioxidant capacity in different tissues of E. sinensis decreased following exposure to 0.70 mg/L of Cu 2+ , indicating that a higher level of Cu 2+ exposure induces oxidative damage. In addition, our data showed a variable intensity of oxidative stress in different tissues after Cu 2+ exposure, which was supported by a previous study in Carassius auratus [ 43 ], indicating the tissue specificity of Cu 2+ toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Our study further showed that the antioxidant capacity in different tissues of E. sinensis decreased following exposure to 0.70 mg/L of Cu 2+ , indicating that a higher level of Cu 2+ exposure induces oxidative damage. In addition, our data showed a variable intensity of oxidative stress in different tissues after Cu 2+ exposure, which was supported by a previous study in Carassius auratus [ 43 ], indicating the tissue specificity of Cu 2+ toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the enzyme activity assay revealed a nearly 80% inhibition of the typical natural enzyme activities in bacteria ( Figure 6 a,b). Copper is able to bind to GR to induce its inactivation, according to the previous study [ 87 , 88 ]. GR can catalyze the reduction of glutathione disulfide (GSSG) to reduced glutathione (GSH) to maintain redox homeostasis in bacteria [ 43 ].…”
Section: Planktonic Bacteriamentioning
confidence: 97%
“…Insufficient intake of copper often leads to anemia, paratrichosis, infertility, and brain disorders [187]. There is also no doubt that copper is toxic at high levels, although it is an essential micronutrient for human bodily functions [188]. An overload of copper quickly results in a detrimental alteration of living organisms, through liver cirrhosis, emesis, diarrhea, arthritis, cognitive decline, and cardiac arrhythmia [187].…”
Section: Coppermentioning
confidence: 99%